Using the ANSYS Workbench software for designing of the miniature unmanned aerial vehicles - Tamila, Yauheniya (Видавництво Львівської політехніки, 2013)
The requirements for the miniature unmanned aerial vehicles which are designed for monitoring of the area in order to prevent and eliminate the natural emergencies are mentioned. ANSYS Workbench software is used for simulation the aerodynamics of the wing and determination the maximum lift angle of attack. Method of strength computing of the wing stiffening element is described.
Keywords: miniature aerial vehicles; emergency situations; strength; aerodynamics; in real time monitoring; flight conditions; starting conditions